Answer:
Step-by-step explanation:
Given:
To find:
Solutions:
First, you have to subtract by 1 from both sides.
[tex]\Longrightarrow: \sf{-3y+1-1=7-2x-1}[/tex]
Solve.
[tex]\Longrightarrow: \sf{-3y=-2x+6}[/tex]
Then, you divide by -3 from both sides.
[tex]\Longrightarrow: \sf{\dfrac{-3y}{-3}=-\dfrac{2x}{-3}+\dfrac{6}{-3}}[/tex]
Solve.
Divide these numbers from left to right.
[tex]\Longrightarrow: \sf{-\dfrac{2x}{-3}+\dfrac{6}{-3}}[/tex]
[tex]\Longrightarrow: \sf{\dfrac{-2x+6}{-3}}[/tex]
[tex]\Longrightarrow: \sf{=-\dfrac{-2x+6}{3}}[/tex]
[tex]\Longrightarrow: \boxed{\sf{y=-\dfrac{-2x+6}{3}}}[/tex]
[tex]\text{Therefore, the correct answer is {y=-$\dfrac{-2x+6}{3}$}}}}[/tex].
I hope this helps, let me know if you have any questions.